Analysis of the dynamic response of the new interchange channel closely under the existing line - Yunsi Liu; Yueyuan Huang; Yu Huang; Yonglin An; Yaxiong Peng (Scientific Reports)
Abstract The vibration caused by the existing operating metro has a negative impact on the construction of new metro lines and the nearby surroundings. The focus of this study is the confined interchange area between Beijing Metro Line 17 and Shilihe Station of Line 10. In the study area, the interchange between Shilihe Station of Line 10 and Line 17 has a confined frame structure that is already in operation without any overburden between the existing line and the new line; therefore, the vibration of the operating subway interferes with the construction. The measured and numerical simulation results show that the vibration response has an attenuating effect in the frame structure from top to bottom, and these studies are related to the train operating speeds of 20 km/h, 40 km/h, 60 km/h and 80 km/h. The type and spacing of the I-beams also have an effect, and the higher the train speed, the greater the vibration response. The principle of equivalent stiffness of I-beam is proposed, and the functional relationship between equivalent stiffness and I-beam parameters is deduced. The models of no vibration amplification effect, weak vibration amplification effect and strong vibration amplification effect are established, and it is obtained that when the I-beam is I20b and the spacing is 0.8 m, the equivalent stiffness is maximum, the vibration response of the frame structure is minimum, the vibration load is attenuated in the frame structure, and the vibration amplification effect of the soil on both sides is smaller. The study of the vibration amplification effect provides some theoretical guidance for the construction of similar projects.